Conjugation of Peroxidase from Brassica oleracea gongylodes for Use as a Label- Prospect of a Novel Enzyme Tag for Immunoassay Systems - Shetty, Premalatha; D’Souza, Avila; CP, Geethu (International Journal of Applied Sciences and Biotechnology, 2017)
Peroxidase tagged proteins are being used successfully as immune-histological probes for the demonstration of tissue antigens, and in enzyme amplified immunoassay systems for the quantitative determination of soluble and insoluble antigens. The glycoprotein nature of peroxidases can be exploited for conjugation to proteins of interest. Peroxidase extracted from the bulbs of Brassica oleracea gongylodes was salted out at 40-80% ammonium sulfate saturation and activated by treatment with 1-Fluoro-2,4-dinitro benzene (FDNB) and periodate. Treatment with 0.08% FDNB and 12.5mM periodate was optimized for activation of the enzyme. The treated enzyme was found to conjugate successfully to immunoglobulin fractions harvested from egg yolk (IgY), human plasma and goat serum. Enzyme conjugated to IgY fraction showed improvement in its pH stability and temperature stability. The affinity of the enzyme for its substrate phenol did not alter to a significant extent upon activation and conjugation. The conjugates exhibited high affinity towards phenol, bromocresol purple and bromothymol blue in comparison to HRP conjugates prepared using the same protocol. Int. J. Appl. Sci. Biotechnol. Vol 5(1): 59-65